2‐Acetyl‐1, 3‐Diacyl–sn‐Glycerols with Unusual Acyl Composition in Seed Oils of the Genus Polygala. Issue 8 (29th June 2018) - Smith, Mark A.; Zhang, Haixia; Burton, Ian W.; Liu, Chao; Cheng, An‐Wei; Sun, Jin‐Yue
Abstract : Seed oils containing unusual triacylglycerol (TAG) molecules, where one fatty acid of a TAG is substituted by an acetate group (Ac), are uncommon but of considerable interest as potential low‐viscosity biofuels and lubricants or reduced calorie food ingredients. Although the properties and pathway of biosynthesis of 3‐acetyl‐1, 2‐diacyl‐ sn‐ glycerols ( sn‐ 3‐acTAGs) have been described, little is known about the occurrence of 2‐acetyl‐1, 3‐diacyl‐ sn‐ glycerols ( sn‐ 2‐acTAGs). Prompted by a report of sn‐ 2‐acTAGs in the seeds of Polygala virgata, a study of the seed oil of seven members of this genus, and two related species is conducted. The presence of sn‐ 2‐acTAG and lesser amounts of conventional TAG is conclusively demonstrated in Polygala seed oil by Matrix‐Assisted Laser Desorption/Ionization Time‐of‐Flight Mass Spectrometry (MALDI‐TOF MS) and high resolution C 13 nuclear magnetic resonance spectroscopy (C 13 NMR). Analysis of seed fatty acids reveals a diversity of composition with oils from P. myrtifolia and P. fruticosa dominated by the medium‐chain fatty acid (MCFA) myristic acid (tetradecanoic acid) at an average of 79.8 and 74.1% of total seed fatty acids, respectively. In contrast, MCFAs are absent from oils from P. tenuifolia and P. virgata, with the very‐long‐chain fatty acid (VLCFA) gondoic acid ( cis ‐11‐eicosenoic acid) being most abundant. Polygala species therefore represent a rich source of sn‐ 2‐acTAGs and uncommon fatty acids. Practical applications : The seed oils of Polygala species contain a highly unusual combination of sn‐ 2‐acTAGs and uncommon fatty acids. These plants can serve as a unique genetic resource for the elucidation of the pathways of biosynthesis of these lipids and the identification of genes for the engineering of novel oils in transgenic plants. As Polygala is morphologically diverse genus ranging from annual herbs to small trees, identification of species with suitable seed production and agronomic characteristics may allow the commercial production of novel oils for specific higher value uses. Plant seed oils are generally composed primarily of triacylglycerol (TAG). In this article, the authors examine the seed oils of seven species in the genus Polygala and report the occurrence of an unusual lipid, 2‐acetyl‐1, 3‐diacyl–sn‐glycerol ( sn ‐2 acTAG). These plants also produce unusual fatty acids in their seed oil, with Polygala tenuifolia being enriched in gondoic acid ( cis ‐11‐eicosenoic acid, 20:1 Δ11 ) and Polygala myrtifolia containing myristic acid (tetradecanoic acid, 14:0). The genus Polygala represents a potential source of novel oil and a resource for the characterization of sn ‐2 acTAG biosynthesis. Abstract : Plant seed oils are generally composed primarily of triacylglycerol (TAG). In this article, the authors examine the seed oils of seven species in the genus Polygala and report the occurrence of an unusual lipid, 2‐acetyl‐1, 3‐diacyl–sn‐glycerol ( sn ‐2 acTAG). These plants also produce unusual fatty acids in their seed oil, with Polygala tenuifolia being enriched in gondoic acid ( cis ‐11‐eicosenoic acid, 20:1 Δ11 ) and Polygala myrtifolia containing myristic acid (tetradecanoic acid, 14:0). The genus Polygala represents a potential source of novel oil and a resource for the characterization of sn ‐2 acTAG biosynthesis.